Respuesta :

Answer:  Slope = -1

===========================================

Work Shown:

Let's apply the slope formula to get...

m = (y2 - y1)/(x2 - x1)

m = (-13 - 10)/(10 - (-13))

m = (-13 - 10)/(10 + 13)

m = -23/23

m = -1

The slope is -1

-----------

Extra info:

The slope is the rate of change. Specifically it's the change in y over the change in x. So that's why we divide the (y2-y1) over the (x2-x1). The (y2-y1) is the change in y; the (x2-x1) is the change in x.

You can think of it as

slope = rise/run

rise = y2-y1 = change in y

run = x2-x1 = change in x